Correlation between Probable or Non-Probable Leptospirosis with Laboratory Findings: Based on Leptospirosis Case Definition and Faine Criteria - Citra Saputra, Rada; Mahmuda, Iin Novita Nurhidayati; Utami, Musrifah Budi; Pinakesty, Angiesta; Mubaraq, Syahrun El; Srirojanakul, Sirada (Institute of Topical Disease Universitas Airlangga, 2025)
The incidence of leptospirosis is increasing globally, and developing countries are no exception. Leptospirosis cases are called the tip of the iceberg phenomenon, even though misdiagnosis, underdiagnosis, and underreporting still occur in health services. Thus, it leads to delays in leptospirosis treatment and may result in increased mortality rate from severe leptospirosis infection (Weil's disease). This study was to establish an accurate diagnosis by optimizing the Faine criteria. This study used an analytical observational design with a cross-sectional approach to examine faine criteria and laboratory examinations. We collected data from medical records from the Karanganyar General Hospital and the PKU Muhammadiyah Surakarta Hospital. We processed the data using SPSS version 25. The total number of samples was 42. They were divided into women (19%) and men (81%). Based on the definition category of leptospirosis cases, there were 2.4% probable group (score criteria faine part A 20-25) and 97.6% not-probable group (score criteria faine part A <20). Bivariate analysis (Chi-Square test) showed that there was no significant correlation between Faine Part A criteria and serological tests in both groups (p=0.874) as well as Hb (p=0.522), thrombocytopenia (p=0.265), leukocytosis (p=0.197), and neutrophilia (p=0.710). Loss of sodium and potassium didn’t show significant data (hyponatremia p=0.174; hypokalemia p=0.311; hypocalcemia p=0.131) not as in tropical diseases. The approach to diagnosis of leptospirosis cannot be performed using only Part A criteria, Faine, even though the patient was included in the probable definition category, even though the Faine Part A criteria score is 20-25 or ≥26.